Multilingual Philippine medical thesaurus on diseases-pathological conditions, signs and symptoms in Cebuano - Bailon, Anne Kristine V. (2003)
Philippines has a diverse culture and a multilingual society. This situation greatly affects the field of medicine, particularly medical informatics. Medical practitioners are English-educated, and medical information sources are largely written in English. But local knowledge are not readily available in English. In this case, tools for information management such as a controlled vocabulary can be valuable for an effective information system. Therefore a thesaurus for medical terms, specializing in Cebuano would be relevant.